Improving Students' Reading Comprehension through Adapted Monopoly Game - Rona Elfiza (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
The study was conducted to improve the students’ reading comprehension in comprehending descriptive text at SMP N 2 Pariaman. The research was carried out due to the low learning outcomes in comprehending reading descriptive text, so creative learning technique that can improve learning outcomes is absolutely needed. Adapted monopoly game was chosen to improve the students’ reading comprehension. This research was classroom action research with two cycles. Each cycle consist four components; they were planning, action, observation and reflection. This research was conducted in class VIII 1 SMPN 2 Pariaman. The class consisted of 37 students. The reason of choosing this class because from the observation in reading activity especially in comprehending descriptive text the students had low ability in reading comprehension. The data were collected through the test and observation sheet. Students’ average score at pre test is 5,3, after using adapted monopoly game at first cycle, it increased into 5,3. Then, after cycles it increased into 7,08. The adapted monopoly game was seen effectively improving students’ reading comprehension in comprehending descriptive text at SMP N 2 Pariaman.